The Solving Indonesian Intellectual Property Rights Transfer Issue - Situmeang, Ampuan; Silviani, Ninne Zahara; Tan, David (Al-Risalah, 2023)
The aim of this research was to analyze legal problems that are hindering the process of intellectual property rights (IPR) transfer within the Indonesian legal system. This objective was achieved by employing the normative legal research method with a statutory approach while, utilizing secondary data. Accordingly, the secondary data used consisted of primary legal sources, including Law No. 30 of 2000 on Trade Secrets, Law No. 20 of 2016 on Trademarks and Geographical Indications, Law No. 28 of 2014 on Copyrights, Law No. 13 of 2016 on Patents, as well as relevant judicial decisions made within the Indonesian legal system, which enhanced the analysis. This research showed the problems that exist within the Indonesian legal system regarding the transfer of IPR and identified the contributing factors. Furthermore, from the analysis conducted, it was found that the Indonesian IPR legal framework is too complex and lacks harmony, specifically when it comes to the mechanisms involved in IPR transfer and the bureaucratic efficiency associated with these processes. This research serves the purpose of providing comprehensive literature for the development of better intellectual property laws, which are continuously being refined by the Indonesian government to protect and foster creativity in the economy of the country, thereby making it a more attractive prospect for capital. Unlike previous studies, this research placed significant emphasis on legal problems specifically hindering the process of IPR transfer and examined their impacts on actual IPR cases within the Indonesian legal system.